(untitled) (Psychology Travelogs, 2023)
The article explores the peculiarities of development in children of early school age, providing a psychological characterization of this age group. Based on the analysis of psycho-pedagogical literature, the essence of the concept of "emotional development" is elucidated, considering it as a crucial aspect of human psyche and behavior. The author identifies and substantiates the psychological features of emotional development in children of early school age, including the intensity of emotions (children of this age often express emotions vividly and intensely, easily experiencing joy, sadness, anger, or excitement); changes in the expression of emotions (children may abruptly change their emotional states without apparent reasons, and a single situation can evoke different emotions at different moments); gradual development of self-regulation (children learn to regulate and control their emotions, although this process evolves gradually, and children may struggle with controlling their emotional reactions); perception of social norms (children start to understand social norms and rules for expressing emotions in specific situations); formation of social relationships (children actively interact with peers and adults, contributing to the development of social skills and group interaction); development of empathy (over time, children develop the ability to perceive and understand the emotions of others, showing empathy and offering support to their peers); formation of identity (children begin to sense their identity and understand their own emotions in the context of personal self-definition); influence of the family environment (family surroundings and relationships with parents and family significantly impact the emotional development of children). The article also explores the interrelation between the learning process in school, socialization, and the formation of emotional intelligence in children. Factors influencing emotional development, including family and pedagogical aspects, are analyzed. The research aims to identify key aspects of emotional development in children of early school age and provide recommendations for optimizing this process in both school and family environments.